Efeito da terapia manual na região craniomandibular e cervical na dor orofacial e amplitude de movimento mandibular em pacientes com disfunção temporomandibular: revisão sistemática - Martins, Rita de Cássia das Neves (2022)
Background: There is an association between TMD and cervical that can be explained by its neuroanatomic and biomechanical relationship between the cervical spine and the stomatognathic system, this relationship contributes to craniofacial and cervical pain. Manual therapy aims to reduce joint and muscle pain (on the face and cervical spine). Objective: is to evaluate the efficacy of manual therapy in the craniomandibular region in patients with TMD and compare with manual therapy in the cervical region under pain intensity and the amplitude of the mandibular movement. MATERIALS AND METHODS: It was performed by systematic review according to the preferential items of systematic reviews and meta-analysis (prism) reports, with sources randomized clinical trials (produced until November 2022) and collected in the basis of Data Medline, PubMed, BVS, Cobse, Pedro, Scielo, Lilacs and Central. Results and Conclusion: Manual therapy in the craniomandibular region with cervical intervention associated with exercise, has a clinically relevant improvement in the intensity of orofacial pain as well as in the amplitude of the mandibular movement. And manual therapy in the cervical region in an associated way or not exercises and/or education to the patient, also have a progressive reduction in the intensity of orofacial pain and gain of clinically important mandibular motion amplitude. Clinical relevance: Manual therapy in the craniomandibular region and cervical manual therapy with or without exercise is beneficial for patients with TMD.